Preliminary study: ?-glucosidase Inhibition Ethanolic Extract from Pogeh-Pogeh (Alpinia denticulata (Ridl.) Holttum) - Putra, Nanda; Al-Amin, Jihan Hanifah; Wahyuni, Fitratul (Jurnal Mandala Pharmacon Indonesia, 2024)
?-glucosidase inhibitor is a potential antidiabetic drug in controlling the blood glucose in diabetic patients. This study aims to screen the inhibitory activity of various parts of Alpinia denticulata against the ?-glucosidase enzyme through in-vitro testing. As a preliminary study, the 70% ethanolic extract of the Alpinia denticulata including rhizome, stem, leaf, and fruit was evaluated for inhibition of ?-glucosidase, together with total phenolic content and the toxicity based on the Brine Shrimp Lethality Test (BSLT). Each part of the plant extract showed a higher IC50 value than acarbose as a positive control (IC50 of fruit extract = 14.39 ?g/ml, IC50 of leaf extract 6.13 ?g/ml, IC50 of stem extract 20.57 ?g/ml, rhizome extract 126.67 ?g/ml and acarbose 172.02 ?g/ml). Interestingly, each of the extract also showed different quantities of total phenolic content in the same order as their IC50 in inhibiting ?-glucosidase activity. Additionally, the BSLT showed that only the leaf and stem are in the non-toxic group. Based on the assay, it suggested that this plant has the potential to be investigated as an antidiabetic drug.